Development of Learning Media for Google Classroom Session in Madrasah - Hilyah Ashoumi; Syahir Naashiruddin; Ahmad Ahsanul Khuluq (Indonesian Journal of Islamic Education Studies (IJIES), 2021)
This research aims to develop teaching materials for google classroom sessions at MTs and MA Nizhamiyah Ploso Jombang. Data collection techniques using questionnaires, validation sheets, and pretest-posttest questions. Therefore, researchers used the R&D method to process questionnaires and the Pairet Sample Test to determine student learning outcomes and meaningful treatment in researching each variable. The research was conducted on 30 7th grade students of Islamic Cultural History subject MTs Nizhamiyah and 30 11th grade students of MA Nizhamiyah Fiqh subject. The results of the research conducted state that: (1) From the average of all the aspects asked in class 7 SKI subject is 69.6% and in class 11 Fiqh subject is 75%, both of which mean feasible It is concluded that learning using Google Classroom learning media at MTs and MA Nizhamiyah Ploso is said to be feasible. (2) The mean score of the pretest class 7 subject to SKI was 52.8, while the posttest score was 68.5 and the mean score of the pretest class 11 Subject Fiqh was 48.1, while the posttest score was 68.1. Based on the table of paired samples test, the significance value is <0.05, indicating that there is a significant influence on the differences in treatment given during the pretest and posttest in Islamic Cultural History subjects MTs Nizhamiyyah and Fiqih MA Nizhamiyyah Ploso Jombang.